The Story of David's Victory in 1 Samuel 17:45-52 and Its Implications for the Attitude of Faith of Today's Christians in Facing Challenges - Fallo, Abryani; langkola, Adinda lestari; Manu, Sendi Marlina; Djawa, Maya (Lembaga Penelitian dan Pendidikan Mandala, 2025)
David's courage in fighting Goliath can be an example for us Christians today, so that we as Christians have the courage to face the challenges we will face in life. David had to fight the Philistines who came armed with swords, spears and javelins and also had to fight Goliath, a giant. However, he came in the name of the Lord of the worlds. David's victory was not only due to his strength or skill in fighting but because of his firm faith and also because of God's guidance. Therefore, we as Christians must have firm faith that we can overcome the challenges and problems we will face because God's presence is always there. The purpose of this writing is how David's victory in his faith contributed to the attitude of Christians in facing challenges today. The research method used is literature study, namely a research method that collects data from existing sources.